Геоінформаційний аналіз економічного ризику природних і техногенних катастроф в Україні - Іванюта, С.П. (Екологічна безпека та природокористування, 2012)
Actual natural and technogenic threats in Ukraine which have a proof tendency to the height during the last years are analysed. Methodology of evaluation of probability of losses and economic risk of extraordinary situations of different origin is considered. On this basis with the use of technologies of the geographic information systems the estimation of economic risk of natural and technogenic catastrophes is carried out in Ukraine.